Minimally Invasive Approach Based on Pterygoid and Short Implants for Rehabilitation of an Extremely Atrophic Maxilla: Case Report. Issue 4 (August 2017) - Cucchi, Alessandro; Vignudelli, Elisabetta; Franco, Simonetta; Corinaldesi, Giuseppe
Abstract : Introduction: Extremely atrophic maxillae can be considered the most important indication for three-dimensional maxillary reconstruction. Different bone-augmentation techniques have been suggested to accomplish this. This article illustrates a minimally invasive approach to rehabilitation of the extremely atrophic maxilla. Material and Methods: A 63-year-old male patient was referred for restoration of his totally edentulous maxilla with a fixed full-arch implant-prosthetic rehabilitation. Four short implants in the premaxillary region and 2 longer implants in the pterygomaxillary regions were inserted with piezoelectric implant site preparation. Discussion: At the 1-year follow-up appointment, no clinical or radiographic changes in the soft-tissue contours or crestal bone levels were observed. Conclusion: This surgical approach, based on the combination of short implants in the premaxillary regions and pterygoid implants in the pterygomaxillary regions, represents a way to shorten treatment timing, minimize the risk of surgical complications, and reduce patient discomfort and costs.